An exploration technique for the interacted multiple ant colonies optimization framework - Aljanaby, Alaa; Ku-Mahamud, Ku Ruhana; Md. Norwawi, Norita (2010)
Interacted Multiple Ant Colonies Optimization (IMICO)is a newly proposed framework. In this framework several colonies of artificial ants are utilized. These colonies are working coopereatively to solve an optimization problem using some interaction technique. Explaration technique is doing an essential job in this framework. This technique is responsible for directing the activity of utilized colonies towards the difference parts of the huge search space. This paper describes the newly proposed IMACO framework and proposes an effectiveexploration technique. Computational tests show that the new exploration technique can furthermore improve the IMICO performance. These tests also show the capability of IMICO to outperform other well known ant algorithms like the ant colony system and max-min ant system.